An assessment of the impact of economic sanctions on Rhodesia’s cattle industry, 1965-1972 (Historia, 2021)
Although there is abundant literature on international sanctions against Rhodesia, it is disturbing to note that most of this literature places little if any emphasis on South Africa’s role in softening the economic impact of the international embargo on Rhodesia’s economy especially in the years 1965-1972. In explaining the ineffectiveness of sanctions, far too much emphasishas been placed on the myth of “Rhodesian ingenuity” rather than on the role played by the 1964 Trade Agreement in facilitating sanctions busting by South Africa and Rhodesia. 1 In contrast, this article attempts to correct this anomaly by focusing on South Africa’s role in saving Rhodesia’s beef industry from total collapse. The study tries to show how the 1964 Trade Agreement came to act as a means through which Rhodesia’s illegal beef exports found their way to the South African market and overseas. Through this Agreement and also the cooperation rendered by South Africa’s allies on the continent, Rhodesia was able to earn enough foreign currency to kick-start agrarian diversification in the northern higher rainfall areas where an export quality beef industry soon emerged. However, as the article implies the gains made by Rhodesia’s beef industry in the period under consideration here were in the end, nullified by a deepening economic and political crisis spawned bysanctions.
Keywords: economic; sanctions; Rhodesia; export market; Afrikaanse Handelsinstituut; beef consumers; diplomatic; government; Ministry of Agriculture; Zimbabwe